A Mrs. Miracle Christmas - Macomber, Debbie ([New York] : Random House Large Print, 2019)
Laurel McCullough's beloved grandmother has just been diagnosed with Alzheimer's and baby she and her husband have longed for seems an impossible dream. She invites Mrs. Miracle into her life and it's not long before they form a beautiful friendship. As her grandmother's condition seems to improve, and Laurel and Zach continue their quest for a child, Laurel soon sees that there is moreto Mrs. Miracle than meets the eye.
Keywords: Mrs. Miracle (Fictitious character) -- Fiction; Nurses -- Fiction; Alzheimer's disease -- Fiction; Christmas fiction; Large type books